Leading meetings and teams : manga for success - Tani, Masumi (Wiley, 2023)
"Shigeo, who works for a building material manufacturing company, is sent to a regional office to improve sales, but instead ends up being overrun by local workers. He tries to actively lead in the internal meetings but ends up ignored. Shigeo runs into Mayumi, a facilitation specialist, and with her advice, Shigeo carefully learns facilitation skills. He slowly starts to win members' buy-ins, builds team motivation, and successfully leads new business projects."--